Crystal structures, thermogravimetric and magnetic properties of four organodiamine templated vanadium oxide frameworks: Influences of diaminoalkane templates - Settheeworrarit T. (2014)
A series of four diaminoalkane templated vanadium oxide polymeric frameworks, [V 2IV O8V 2V O2](C2H10N2), [V 2IV O8V 2V O 2](C3H12N2), [V 4IV O10V 2V O4](C 4H14N2) and [V 4IV O10V 2V O4](C5H 16N2), have been successfully prepared under hydrothermal conditions. The crystal structures are fully characterized revealing layered structures composed of common inorganic building units, namely V IVO5 square pyramids and VVO4 tetrahedra. The layer registries are different depending on the molecular structure of the diaminoalkanes, and can be accounted for by the organic-inorganic interface interactions. The analysis of hydrogen bonds indicates their important role in directing two- and three-dimensional structural architectures. The influences of different diaminoalkanes are also apparent in both thermogravimetric and complex magnetic behaviors, and are discussed in details. © 2007 Springer Science+Business Media, LLC.